An improved Neural Kalman Filtering Algorithm in the analysis of cyclic behaviour of concrete specimens - Krok, Agnieszka (Computer Assisted Methods in Engineering and Science, 2011)
The article is related to the results of research on Node Decoupled Extended Kalman Filtering (NDEKF) as a learning method for the training of Multilayer Perceptron (MPL). Developments of this method made by the author are presented. The application of NDEKF and MPL and other methods (pruning of MLP, Gauss Process model calibrated by Genetic Algorithm and Bayesian learning methods) are discussed on the problem of hysteresis loop simulations for tests of compressed concrete specimens subjected to cyclic loading.